Developing Local Creativity in Songa Village by Utilizing Natural Products Around the Environment - Yustina Selong; Wanda Giovani; Yumita Yumita; Iren Iren; Eksel Jepon (International Journal of Public Devotion, 2022)
Community service is one of the main duties of a lecturer. The activity with the theme "Developing Community Creativity by Using Surrounding Natural Products" was carried out in Songga Village, Menyuke District, Landak Regency, West Kalimantan. The purpose of this activity is to provide motivation and knowledge to the local community regarding creativity in utilizing the natural products that are around them in the form of handicrafts. Through training activities, the community got new experience and knowledge about business opportunities that have a selling value which are able to increase income if then the handicrafts are sold to the market or to souvenir shops. Therefore, participants who took part in the training also gain awareness to hone their skills in making handicrafts made from Sake’ (pandan duri), Sake’ Mansio (Nipah leaves / palm leaves), bamboo, and Banar stems (rattan).